Effects of psychosocial interventions on behavioural problems in youth: A close look at Cochrane and Campbell reviews. (3rd October 2016) - Karlsson, Patrik; Bergmark, Anders; Lundström, Tommy
Abstract : Research indicates that a number of psychosocial interventions are effective for reducing behavioural problems in youth. These interventions are now often included on best practice lists aiming to facilitate informed treatment choices among practitioners. However, analyses in neighbouring research areas have highlighted serious shortcomings in how primary studies are analysed and how studies are synthesised in research reviews. This study took a closer look at the evidence of efficacy for psychosocial interventions that aim to reduce behavioural problems in youth, as shown in systematic research reviews by the Cochrane and the Campbell Collaborations ( n  = 8). The findings suggest a bias towards overemphasising the efficacy of the interventions in several reviews, an over‐confidence in the validity of the findings in some reviews and, overall, a somewhat uncertain evidence base for the efficacy of the interventions. Systematic reviews are crucial for summarising research but more attention to methodological issues may be needed in this area.